(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The ability to report adverse drug reactions (ADRs) is a critical competency for healthcare providers. Healthcare providers must enhance their pharmacovigilance (PV) and adverse drug reaction (ADR) reporting knowledge, attitude, and practice (KAP) if reporting rates are to increase. It has been shown in earlier research that nursing students do not have enough understanding about pharmacovigilance (PV) and how to report adverse drug reactions (ADRs). For that reason, researchers at a Saudi tertiary care teaching hospital set out to determine how pharmacovigilance education affected the beliefs, practices, and abilities of nursing students. A total of ninety nursing students from a Saudi Arabian tertiary care teaching hospital participated in this interventional investigation. We gave each participant an explanation of the study’s goals and had them fill out a questionnaire about their pharmacovigilance knowledge, attitude, and practice. At the conclusion of the intervention, participants were asked to fill out the post-KAP questionnaire again, and the results were analyzed using a Chi-square test. With a ratio of 1:2, the study included 90 nursing students, with an average age of 21.52 ± 1.11 years. Prism v10.1.0 from Graph Pad was used to conduct all statistical computations. After the educational session, participants’ attitudes towards pharmacovigilance changed significantly, and there were notable variations in their grasp of the topic between before and after the intervention. The percentage of students who were informed about pharmacovigilance and adverse drug reaction forms was much higher.